Analisis Kesiapan Guru dalam Mengimplementasikan Kurikulum Merdeka pada Pendidikan Anak Usia Dini - Wulan Tini (Institut Madani Nusantara, 2024)
Curriculum changes in Indonesia demand adaptive readiness from teachers, especially at the Early Childhood Education (PAUD) level. The implementation of the Independent Curriculum at the Early Childhood Education (PAUD) level demands a transformation in teacher readiness. Teachers are the spearhead of education, where teachers are required to be ready to swiftly face the many changes in education, especially to curriculum changes that usually change when related officials change. This study aims to analyze the readiness of PAUD teachers in Katapang District, Bandung Regency, in implementing the Independent Curriculum, reviewed from three main aspects: cognitive readiness (conceptual understanding), affective readiness (attitude/motivation), and psychomotor readiness (pedagogical/practical).This study used a qualitative descriptive method. Data were collected through structured questionnaires and in-depth interviews with 15 teachers selected using a purposive sampling technique. The results showed that teachers' affective readiness was in the high category, characterized by strong motivation to change. However, cognitive and psychomotor readiness remained in the medium to low category. The main obstacles identified included difficulties in developing teaching modules, designing Authentic Assessments, and integrating the Pancasila Student Profile Strengthening Project (P5) appropriate to the characteristics of early childhood. This study recommends the need for intensive community-based mentoring through the Early Childhood Education Cluster Activity Center (PKG) at the sub-district level.